Gigoo, Arvind, The Ugly Kashmiri (Cameos in exile), (2ª ed.), Nueva Delhi, Allied Publishers, 2008, 108 pp. - Nair, Hari (El Colegio de México, 2009)
Gigoo, Arvind, The Ugly Kashmiri (Cameos in exile), (2ª ed.), Nueva Delhi, Allied Publishers, 2008, 108 pp.